ANALISIS SENTIMEN PENGGUNA TWITTER TERHADAP ROKOK ELEKTRIK (VAPE) DI INDONESIA MENGGUNAKAN METODE NAÃVE BAYES - Aditya, Dio Rizki; Supriyati, Endang; Listyorini, Tri (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2022)
Social media such as Twitter is a communication medium that is in great demand by Indonesian people from various groups. Many of the people who express opinions or opinions on something, from good things to bad things or criticize on twitter. Because of this, making e-cigarettes or commonly called vapes as an object of analysis, which has many users of e-cigarettes or vapes in Indonesian society from teenagers to adults. Making user opinions or opinions on Twitter in the form of tweets which will later be used for sentiment analysis, where we can determine the sentiment of each tweet, in the form of positive, negative, and neutral sentiments. Retrieval of tweet data on twitter we use the twitter API that has been provided by the twitter developer. Using a program created using the python programming language and using the NaÃ¯ve Bayes classification model. From the sentiment analysis carried out using the NaÃ¯ve Bayes classification model, with an accuracy rate of 77.5%, the number of negative polarity 11.7%, the number of neutral polarity 77.3%, and the number of positive 11%.